Economic freedom and foreign direct investment in developing countries - Quazi, Rahim R.; Rashid, Shahidur (Project MUSE, 2007)
This paper employs cross-country growth regressions for a sample of developing countries to examine the determinants of FDI. In addition to economic factors affecting foreign direct investment, the analysis also tests for the role of institutional quality (enforcement of property rights, corruption, etc.) and policy orientation factors (openness). The paper evaluates whether foreign investment responds to changes in levels of economic freedom. In addition it tests whether the insignificant coefficient found in previous studies is the result of the level of aggregation in the economic freedom data. Finally, it disaggregates the data on economic freedom and re-estimates the relationship between FDI and components of economic freedom. Foreign direct investment is found to vary positively with increases in certain components of economic freedom.